“Few” or “Many”? An Adaptation Level Theory Account for Flexibility in Quantifier Processing - Heim, Stefan; Peiseler, Natalja; Bekemeier, Natalia (Frontiers in Psychology, 2020)
Quantifiers (e.g. “many”, “some”, “at least 7”, “more than half”) are words characterising amounts or numerosities by reference to an internal threshold, or degree. For some quantifiers, this degree is not uniquely defined: It varies for external contexts (“many lions”/“many flies”) but may also be shifted within an individual (“many fries” for a hungry/full person). Previous studies showed that manipulation of the degree for one quantifier can impact that of other quantifiers. In this study, we tested whether such changes can occur by mere habituation, as formalised in the Adaptation Level Theory by Helson (1948) for sensory stimuli such as brightness or weight. To this end, participants read a quantifier statement and then judged whether a visual display with varying amounts (20-80%) of blue and yellow circles matched that statement. In Block 1, we identified which proportion of circles of a given colour was judged by participants as “many” or “few”. In Block 2, we modified the presentation of stimuli such that (1) only the quantifier “many” was used and (2) only low proportions of circles of a given colour were presented, thus changing the base rate at which proportions were encountered together with “many”. The hypothesis was that the internal degree of what is interpreted as “many” would be shifted downwards, and that this shift would also affect judgements of “few”. Block 3 was identical to Block 1, serving as a test for the expected effect on the degree/threshold for/across all proportions. The findings were as expected: The probability of accepting 40% as “many” was increased during Block 2, indicating adaptation. Likewise, the probability function for “few” was shifted in a parallel fashion around proportion 40%. These findings complemented earlier studies demonstrating intra-individual flexibility in quantifier processing. They show that this flexibility can even be observed in the absence of explicitly stated verbal contexts or reinforcements, in line with the Adaptation Level Theory formulated originally for magnitudes, i.e. non-linguistic representations of quantities.